"Funds" Statements: A Historical Perspective. - Rosen, L. S.; DeCoster, Don T. (The Accounting Review, 1969)
Abstract The article discusses the historical perspectives of "Funds Statement." The American Institute of Certified Public Accountants completed a research study on the subject of "funds" statements in 1961 and issued an Opinion of the Accounting Principles Board in 1963. The official pronouncement was the first on "funds" statements by a major accounting body and has had the effect of increasing the use of "funds" statements in corporate annual reports. The basic theme of this article is that needless confusion in preparing and interpreting "funds" statements in corporate annual reports still exists after a century of discussion and practice. The "funds" statement is being required to report all items of financial information and perspectives not disclosed by the income statement, balance sheet and statement of retained earnings. This means that the "funds" statement must report changes in some definition of liquidity, reveal all important "inter-entity" transactions, somehow reconcile the cash and accrual bases of accounting, be flexible, report different perspectives and readily communicate with laymen.